Business Model Canvas : The Spices Packaging / Siti Mudzalifa Anuar - Anuar, Siti Mudzalifa (2020)
The Spices Packaging name actually came from the main function of my product and it is suitable for my type of product. Spices is a seed, fruit, root, bark, or other plant substance primarily used for flavouring, colouring or preserving food. Spices are distinguished from herbs, which are the leaves, flowers, or stems of plants used for flavouring or as a garnish. As spices are being used every day for cooking, it demand become higher. Furthermore, nowadays more company produced their own spices to fulfil the demand in the market. Today, there are many spices company such as Adabi, Alagappa and Baba’s as the demands that keep increasing. It is evident that the spices industry in Malaysia is experiencing rapid growth. Malaysia has the necessary ingredients to develop the industry to its full potentials. Provision of better infrastructures especially in the export of the spices is essential. The Spices Packaging functioning in packing the spices especially for the small scale company. This appliance will save time for the co-worker to pack the spices and increase the company production in a day. This appliance can increase the hygiene in the factory to process the spices especially for the packaging process. I focused to expand this product in the Asian especially South Asia